2008
DOI: 10.1007/s10548-008-0064-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Correspondence Between Functional MRI (fMRI) Activations and Cortical Current Density Maps of Event-Related Potentials (ERP): A Study with Four Tasks

Abstract: We investigated the spatial correspondence between functional MRI (fMRI) activations and cortical current density maps of event-related potentials (ERPs) reconstructed without fMRI priors. The presence of a significant spatial correspondence is a prerequisite for direct integration of the two modalities, enabling to combine the high spatial resolution of fMRI with the high temporal resolution of ERPs. Four separate tasks were employed: visual stimulation with a pattern-reversal chequerboard, recognition of ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Sources of CSD are supposed to be located in the cortex (Srinivasan 2005 ). Consistent with the present results, previous studies reported that BOLD responses could be estimated from cortical current density distribution in simultaneous fMRI and EEG recording (Liu and He 2008 ; Minati et al 2008 ). These results strongly suggest that the present GLM system using simultaneous NIRS and EEG recording could assess neuro-hemodynamic coupling in the parietal cortex.…”
Section: Discussionsupporting
confidence: 93%
“…Sources of CSD are supposed to be located in the cortex (Srinivasan 2005 ). Consistent with the present results, previous studies reported that BOLD responses could be estimated from cortical current density distribution in simultaneous fMRI and EEG recording (Liu and He 2008 ; Minati et al 2008 ). These results strongly suggest that the present GLM system using simultaneous NIRS and EEG recording could assess neuro-hemodynamic coupling in the parietal cortex.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to fMRI-informed EEG, no specific assumption is made about the spatial organization of activation patterns. This implies that this strategy can yield effects in brain structures or networks that are not necessarily the biophysical generators of, say, the ERP recorded at the scalp (Debener et al, 2005;Minati et al, 2008). One also has to bear in mind that single EEG epochs contain high levels of noise, and single-trial EEG analyses therefore have to rely on techniques that increase the signal-to-noise ratio of individual trials.…”
Section: Eeg-informed Fmrimentioning
confidence: 99%
“…272,279,282 Co-registration of data acquired through high-density EEG and/or MEG recordings with structural neuroimaging, such as MRI, provides information about brain activity with spatial resolutions comparable to those of fMRIespecially when guided by fMRI-determined regions of interest for a particular brain state or function. [283][284][285][286][287][288] Additionally, most EEGbased recording systems are relatively inexpensive and portable, compared with currently available structural and functional neuroimaging technologies, making them easily deployable in both clinical and naturalistic (i.e., sports, in-theater) settings. The combination of high temporal resolution, reasonable spatial resolution, flexibility of use, portability, and relatively low cost make clinical electrophysiological techniques appealing methods with which to evaluate persons with TBI and disturbances in psychological health.…”
Section: Electrophysiologic Techniquesmentioning
confidence: 99%